Analisis Desk Research Kebijakan Technology Transfer Office Sebagai Solusi Hambatan Teknologi Transfer di Lembaga Litbang Indonesia - Aditya Wisnu Pradana; Anugerah Yuka Asmara; Budi Triyono; Ria Jayanthi; Anggini Dinaseviani; Purwadi; Wahid Nashihuddin (Research and Development Agency Ministry of Home Affairs, 2021)
The government-owned research and development institutions (lembaga litbang) has been established for a long time; units under the ministries, universities, or an independent institution structure called the Non-Ministry Government Institutions in the field of Research and Technology (LPNK Ristek). However, the long course of LPNK Ristek is measured to be not in line with the output of the research and development (R&D) due to its minimal contribution in commercializing the results to its users. This study aims to provide a depth understanding of the form of policy design as the result of low commercialization of R&D results in Indonesia along with existing technology transfer policies. This study also proposes new policy alternatives, namely the Technology Transfer Office (TTO) to improve the existing policy. The approach of this study is qualitative with the desk research method, where the data sources used are obtained through secondary sources from written documents, scientific journals, scientific books, archives, related policies or regulations, and searches from the websites of related institutions. The data sources were published in the period 1996 to 2020. The results of this study found that there were three obstacles to technology transfer in Indonesian R&D institutions, namely the lack of funding, limited quality and quantity of human resources, and a rigid institutional structure that hindered the function of technology transfer. This study also recommends the TTO policy as an alternative technology transfer policy with four main instruments, namely (1) the government activities involved, (2) the structure of the delivery system either directly or indirectly, (3) the degree of centralization, and (4) the degree of automation with funding mechanisms, human resources, and institutions in the form of a Public Service Agency (BLU).